Neurophysiological Determinants of Theoretical Concepts and Mechanisms Involved in Pacing - Roelands, Bart; de Koning, Jos; Foster, Carl; Hettinga, Floor; Meeusen, Romain (Sports medicine (Auckland), 2013)
Fatigue during prolonged exercise is often described as an acute impairment of exercise performance that leads to an inability to produce or maintain a desired power output. In the past few decades, interest in how athletes experience fatigue during competition has grown enormously. Research has evolved from a dominant focus on peripheral causes of fatigue towards a complex interplay between peripheral and central limitations of performance. Apparently, both feedforward and feedback mechanisms, based on the principle of teleoanticipation, regulate power output (e.g. speed) during a performance. This concept is called ‘pacing’ and represents the use of energetic resources during exercise, in a way such that all energy stores are used before finishing a race, but not so far from the end of a race that a meaningful slowdown can occur. It is believed that the pacing selected by athletes is largely dependent on the anticipated exercise duration and on the presence of an experientially developed performance template. Most studies investigating pacing during prolonged exercise in ambient temperatures, have observed a fast start, followed by an even pace strategy in the middle of the event with an end sprint in the final minutes of the race. A reduction in pace observed at commencement of the event is often more evident during exercise in hot environmental conditions. Further, reductions in power output and muscle activation occur before critical core temperatures are reached, indicating that subjects can anticipate the exercise intensity and heat stress they will be exposed to, resulting in a tactical adjustment of the power output. Recent research has shown that not only climatic stress but also pharmacological manipulation of the central nervous system has the ability to cause changes in endurance performance. Subjects seem to adapt their strategy specifically in the early phases of an exercise task. In high-ambient temperatures, dopaminergic manipulations clearly improve performance. The distribution of the power output reveals that after dopamine reuptake inhibition, subjects are able to maintain a higher power output compared with placebo. Manipulations of serotonin and, especially, noradrenaline, have the opposite effect and force subjects to decrease power output early in the time trial. Interestingly, after manipulation of brain serotonin, subjects are often unable to perform an end sprint, indicating an absence of a reserve capacity or motivation to increase power output. Taken together, it appears that many factors, such as ambient conditions and manipulation of brain neurotransmitters, have the potential to influence power output during exercise, and might thus be involved as regulatory mechanisms in the complex skill of pacing.